Primary prophylaxis with G-CSF may improve outcomes in patients with newly diagnosed stage III/IV Hodgkin lymphoma treated with brentuximab vedotin plus chemotherapy. Issue 12 (14th October 2020) - Straus, David; Collins, Graham; Walewski, Jan; Zinzani, Pier Luigi; Grigg, Andrew; Sureda, Anna; Illes, Arpad; Kim, Tae Min; Alekseev, Sergey; Specht, Lena; Buccheri, Valeria; Younes, Anas; et al.
Abstract: We investigate the impact of granulocyte-colony stimulating factor (G-CSF) primary prophylaxis (G-PP, N  = 83) versus no G-PP ( N  = 579) on safety and efficacy of brentuximab vedotin plus doxorubicin, vinblastine, and dacarbazine (A + AVD) in the ECHELON-1 study of previously untreated stage III/IV classical Hodgkin lymphoma. G-PP was associated with lower incidence of ≥ grade 3 neutropenia (29% versus 70%) and febrile neutropenia (11% versus 21%). Fewer dose delays (35% versus 49%), reductions (20% versus 26%), and hospitalizations (29% versus 38%) were observed. Seven neutropenia-associated deaths occurred in the A + AVD arm; none received G-PP. A + AVD with G-PP was associated with decreased risk of a modified progression-free survival event by 26% compared with A + AVD alone (95% CI: 0.40–1.37). G-PP reduced the rate and severity of adverse events, including febrile neutropenia, reduced treatment delays, dose reductions, and discontinuations, and may thus improve efficacy outcomes. These data support G-PP for all patients treated with A + AVD.